Kolektivne traume i strip: Maus, Palestine, Persepolis. - Tomić, Janica (Array, 2008)
The paper deals with examples of graphic novels (or, alternatively, 'comics' or 'comix') about Holocaust, 9/11 and other collective traumas, comments on different ways of narrating such historical events in this media and the controversy around it, referring to critical (especially local) and theoretical readings, e.g. Hayden White's reading of Spiegelman's Maus.